A Literature Review of Total Quality Management Practices in Malaysia and Indonesia Schools - Syaifullah Syaifullah; Ria Mardiana Yusuf; Zainur Hidayah; Ami Pujiwati (International Journal of Social Service and Research, 2023)
The rapid growth of information and technology has encouraged all organizations including school organizations to adopt a quality management called Total Quality Management (TQM). The practice of TQM in Malaysian and Indonesian schools shows similarities and differences. Therefore, this research seeks to explore some of the TQM models and elements that are applied in Malaysian and Indonesian schools. Using a qualitative literature study approach, this study uncovers the models and elements of TQM practiced in Malaysian and Indonesian schools. The TQM models found are the Deming model (PDCA), Quality Circles (QC), Total Quality Control (TQC). The elements of TQM that are practiced include leadership, employee commitment, continuous improvement, employee involvement, training, and customer satisfaction. The difference is that the TQM that is practiced in Malaysian schools found the Crosby "zero defect" model, meanwhile, in Indonesian schools found the Control Chart (CC) Model. The TQM element in the form of problem solving in Malaysian schools is proven to be able to train students' thinking skills, creativity, and innovation. Therefore, Indonesian schools need to adopt it in classroom learning.